Pengaruh Kualitas Pelayanan, Harga, Terhadap Kepuasan Konsumen Menggunakan Jasa Transportasi Gojek Pada Mahasiswa UHN Medan - Siregar, Nia Astuti; Siagian, Nalom; Sinaga, Kepler (Research and Community Service UNIVERSITAS KALBIS, 2025)
In the era of the development of information and communication technology has brought significant changes in various sectors, including the transportation industry. This study aims to analyze the effect of service quality and price on customer satisfaction in using Gojek online transportation services, focusing on students of HKBP Nommensen University Medan. The method used is a quantitative approach with data collection techniques through questionnaires distributed to respondents. The results of the study indicate that Service Quality and Price significantly affect Service Satisfaction, this is shown in the results of the partial test (t test) T-count value (X1) 10.572> t table 1.985 significance value 0.000 <0.05 and the results of the partial test (t test) T-count value (X2) 18.148> t table 1.985 significance value 0.000 <0.05. The conclusion in this study is that Service Quality and Price have a positive and significant effect on Customer Satisfaction.